2003
DOI: 10.7589/0090-3558-39.2.366
|View full text |Cite
|
Sign up to set email alerts
|

Venous Blood Gases and Lactates of Wild Loggerhead Sea Turtles (Caretta Caretta) Following Two Capture Techniques

Abstract: During summer of 2001, venous blood gases were determined in loggerhead sea turtles (Caretta caretta) captured by trawl (nϭ16) in coastal waters of South Carolina and Georgia (USA) as part of a sea turtle census program and captured in pound nets (nϭ6) in coastal North Carolina (USA) during a study of sea turtle population biology. Trawls were towed for 30 min, so turtles captured were forcibly submerged for Յ30 min. Pound nets are passive gear in which fish and sea turtles are funneled into a concentrated are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 18 publications
8
77
3
1
Order By: Relevance
“…These findings agree with previous research suggesting that water temperature, regardless of the oxygen content, can limit duration of survival (Ultsch 1989). Similar studies have assessed the physiological effects of various types of fishing gear, such as trawl nets (Stabenau et al 1991, Harms et al 2003 and gillnets (Snoddy et al 2009) on blood physiology of marine turtles and have shown similar effects of entrapment on blood physiology as our study.…”
Section: Discussionsupporting
confidence: 82%
“…These findings agree with previous research suggesting that water temperature, regardless of the oxygen content, can limit duration of survival (Ultsch 1989). Similar studies have assessed the physiological effects of various types of fishing gear, such as trawl nets (Stabenau et al 1991, Harms et al 2003 and gillnets (Snoddy et al 2009) on blood physiology of marine turtles and have shown similar effects of entrapment on blood physiology as our study.…”
Section: Discussionsupporting
confidence: 82%
“…The explanation of this disparity remains uncertain, but could be attributed to different factors, including species, time of forced submergence, water temperature, movement capabilities when submerged (Berkson's animals in the chamber were fastened to a board with very restricted movement inside the chamber), and the previous diving profile of exposed individuals. Situations in which wild sea turtles are forcibly submerged due to entrapment in fishing gear suggest that behavioral and physiological responses are drastically different from what has been recorded under controlled laboratory conditions (Berkson 1966, Lutz & Bentley 1985, Lutz & Dunbarcooper 1987, Harms et al 2003, Stabenau & Vietti 2003, Snoddy et al 2009, Southwood 2013.…”
Section: Key Facts For the Finding Of Ge In Sea Turtlesmentioning
confidence: 95%
“…Multiple studies have revealed that entanglement in fishing gear has significant effects on the physiology of sea turtles (Lutz & Dunbarcooper 1987, Harms et al 2003, Stabenau & Vietti 2003, Snoddy et al 2009, Snoddy & Southwood Williard 2010 but have never described DCS. Various factors may have contributed to the discovery in the current study, including close collaboration with fishermen allowing access to alive and fresh dead bycaught animals, capacity for intensive medical evaluation following capture, availability of modern imaging technology, and familiarity with diving animals and pathology related to GE.…”
Section: Key Facts For the Finding Of Ge In Sea Turtlesmentioning
confidence: 99%
“…Capture by trawl and gillnet often results in forced submergence, which necessitates increased reliance on anaerobic metabolism and, consequently, more pronounced increases in lactate [10,13]. Lactate accumulation may require a recovery period, during which turtles could be vulnerable to boat strike or predators.…”
mentioning
confidence: 99%